THE IMPLEMENTATION OF INDIRECT CORRECTIVE FEEDBACK ON AL-FALAH JUNIOR HIGH SCHOOL STUDENTS’ COMPOSITIONS (RETAIN, 2014)
Abstrak Feedbackadalahbagianpentingdalam proses pembelajaranmenulisdenganmenstimulasisiswauntukmenulislebihbaik(Bitchener & Knoch, 2008; Littleton, 2011; Mi, 2009; Purnawarman, 2011; Reigeluth, 1999). DalampraktekEFL di Indonesia, indirect corrective feedback(ICF)adalahteknik yang seringdigunakandalammengoreksitulisansiswakarenadipercayadapatmenstimulasisiswauntukmenulislebihbaik.Olehkarenaitu, menggunakandesainpenelitiandeskriptifkualitatif, penelitianinibertujuanuntukmendeskripsikanpenggunaanICFpadakarangansiswadalam proses pembelajaranmenulisdeskriptifteks di SMP Al-Falah, menganalisatulisansiswa, danmengetahuiresponsiswaataspengimplementasianICF.Catatanlapanganmenunjukkanbahwa guru sudahmenerapkanICFsesuaidenganprosedur yang diterapkanoleh Coffin et al (2003) and Hartshorn et al (2010). Selainitu, hasilanalisakesalahandalamtulisansiswamenunjukkanbahwamerekamenulislebihbaiksetelahICF diterapkan.Sebagaitambahan, data darikuesionermenunjukkanbahwaICF membantusiswadalammengenalitipekesalahan yang merekabuatdanbagaimanacaramengoreksikesalahansendiri.Kesimpulannya, ICFtelahditerapkandenganbaikdanbenarpadatulisansiswakarenaterbuktiefektifdanguru telahmengikutiprosedur yang dianjurkanoleh para penelitisebelumnya. Kata kunci: indirect corrective feedback, karangansiswa, teksdeskriptif Abstract Feedback comes as a vital part in teaching writing process by stimulating students to write better (Bitchener & Knoch, 2008; Littleton, 2011; Mi, 2009; Purnawarman, 2011; Reigeluth, 1999). In the practice of EFL in Indonesia, indirect corrective feedback (ICF) is regarded as a preferable technique in providing correction on students’ compositions for it is believed to be able to stimulate students to write better. Therefore, using descriptive qualitative research design, this study aimed to describe the implementation of ICF on students’ compositions in the process of teaching descriptive writing in Al-Falah Junior High School, analyse students’ composition, and gather students’ responses toward the ICF given. The data from the field notes revealed that the teacher implemented ICF in such a way following up the procedures proposed by Coffin et al (2003) and Hartshorn et al (2010). Furthermore, the analysis of errors on students’ compositions confirmed that they wrote better after the provision of ICF. In addition, data from questionnairepresented that ICFhelped students recognise the types of errors they made and the way to provide self-correction. In sum, ICF had been well implemented on students’ composition for it was effective and followed the procedures proposed by the previous researchers. Keywords: indirect corrective feedback, students’ compositions, descriptive text